The Influence of Sophisticated Information Technology, Top Management Support and Personal Technical Ability on the Effectiveness of Accounting Information Systems - Kadek Meliana Dewi; I Gst Ayu Eka Damayanthi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to examine the influence of information technology sophistication, top management support and personal technical capabilities on the effectiveness of accounting information systems. This research was conducted at the Denpasar City Regional Apparatus Organization (OPD), the number of samples used was 40 respondents using a non-probability sampling method using a purposive sampling technique. The collected data was then analyzed using Partial Least Square (PLS). The research results show that the sophistication of information technology, top management support and personal technical abilities have a positive effect on the effectiveness of the accounting information system. The implications of this research include two things, theoretical implications and practical implications. The theoretical implications of this research relate to the development of theories regarding the variables of information technology sophistication, top management support and personal technical abilities that support the Technology Acceptance Model (TAM) theory. The practical implications of this research relate to the contribution of research in Denpasar City Regional Apparatus Organizations (OPD) as material for consideration in improving the effectiveness of accounting information systems.